Native beans diversity of different regions from state of Puebla - Ramírez-Pérez Ana Rosa; Díaz-Ruiz Ramón; Jacinto-Hernández Carmen; Paredes-Sánchez Juan Alberto; Garza García Ramón (Revista Mexicana de Ciencias Agrícolas, 2018)
Common bean is basic crop in Mexico with great variability in its morphological characteristics. RAPD is among molecular markers, which have been used in studies about genetic diversity. The aim of this work was to characterize by morphological, agronomical, quality characters and RAPD markers the varieties harvested in different localities from state of Puebla. DNA extraction was made from sample of young leaves of varieties planted under greenhouse. 7 RAPDs starters from OPERON Technologies were used. Polymorphical bands were coded by presence and absence. With NTSYS pc 2.2 software dendrogram was created using Dice’s similarity index, with cut level at value of 0.48 where 13 groups were defined. Six groups were comprised by single variety, 4 groups by 2 varieties, 2 groups by 3 varieties and one group by 7 varieties. The defined groups were comprised by different grain colors and coincided in other morphological characteristics like days to flowering, cooking time and protein content.